Analysis Of Determining The Optimal Capital Structure At PT. Kimia Farma (Persero) Tbk - Yohanis Tasik Allo; Ferdimanto Karaeng (Journal of Entrepreneur, Business and Management, 2023)
This research aims to find out whether the capital structure at PT. KIMIA FARMA (Persero) Tbk from the 2019-2022 time period is optimal or not, and predicts in 2023 how much percentage of own capital profitability must be achieved and the comparison between loan capital and own capital so that the capital structure at PT. KIMIA FARMA (Persero) Tbk can be optimal.  The method used in this research is descriptive analysis using ratios. The type and source of data that will be used in this research is quantitative data. The data source used is in the form of secondary data where the data used by researchers from related companies regarding financial sources and reports. If according to the trend of total capital, then total capital in 2023 will be IDR 13,414,638,284,128, so in order for the profitability of own capital to increase, the company must use 29% of borrowed capital and 71% of its own capital at EBIT of IDR 1,015,887,717,583. In order for this company to be more flexible in changing its capital structure, both of them will achieve Economic Profitability that is greater than the interest on loan capital, or must be more than 15.11%. In conditions where company achieve Economic Profitability is still smaller than capital interest, the loan capital structure should be lowered, or smaller than the own capital structure.